Artikel Review Pemanfaatan Tanaman Pisang (Musa Paradisiaca L.) sebagai Sediaan Kosmetik - Firda Ekayanti, Ni Luh; Megawati, Fitria; Anita Dewi, Ni Luh Kade Arman (Usadha, 2023)
Banana plant (Musa paadisiaca L.)is a type of herbaceous fruit. The banana plant consists of roots, stems, leaves, flowers and fruit. The purpose of this article review is to find out the benefits of banana plants as cosmetic preparations. The content of banana plants include flavonoids, tannins, alkaloids, saponins and others. The type of research method used in review article is to use a literature review, by collecting journals and evaluating information from several journals or guidelines related to the use of banana plants (Musa paradisiaca l.). Banana plants can be used as cosmetic preparations in the form of pell off, loose powder, sheet mask, liquid soap, cream hair polish, lotion and gel. The parts of the banana plant that are used as cosmetic preparations are the banana weevil, stem, midrib, banana leaf, banana peel, and banana heart midrib. Keywords : banana plant for skin, banana plant cosmetics